A cross sectional study of the independent effect of occupation on lung function in British coal miners. Issue 2 (February 1996) - Lewis, S; Bennett, J; Richards, K; Britton, J
Abstract : BACKGROUND: Chronic bronchitis and emphysema are now recognised complications of occupational exposure to coal dust, and since 1992 compensation has been available for miners with impaired lung function provided that they also have x ray film evidence of pneumoconiosis. However, many miners with heavy exposure to coal dust and impairment of lung function therefore do not qualify for compensation because they do not have simple pneumoconiosis. In the present study attempts were made to determine whether coal mining is an independent risk factor for impairment of lung function in a group of Nottinghamshire miners with no evidence of simple pneumoconiosis, by comparing these men with a group of local controls who were not occupationally exposed. METHOD: Forced expiratory volume in one second (FEV1) and forced vital capacity (FVC) were obtained on 1286 miners with no evidence of pneumoconiosis on x ray film. Lung function data were also obtained from a random sample of 567 men aged between 40 and 70 living in a district of Nottingham and who had never worked in the mining industry or in any other dusty occupation. Multiple linear regression in SPSS was used to estimate the mean independent effect of mining on FEV1 and FVC after adjustment for age, height, and smoking, in all miners and controls, and in a subgroup of men of 45 and under. In men of 45 and under, the independent effects of mining and smoking on the probability of a deficit of one litre or more from modelled predicted FEV1 values were computed with logistic regression in EGRET. RESULTS: There was a significant mean effect of mining on FEV1 after adjustment for age, height, and smoking of -155 ml (95% confidence interval (95% CI) -74 to -236 ml, P < 0.001), but the size of effect was inversely related to age such that in men of 45 and under the estimated mean effect of mining was -251 ml (95% CI -140 to -361 ml, P < 0.001). In this subgroup of younger men, 4.7% of miners and 0.7% of controls had a deficit of one litre or more from predicted FEV1 values, and in logistic regression, there was a marginally significant independent effect of both smoking (P = 0.05) and mining (P = 0.07) for a deficit of this magnitude. CONCLUSIONS: Occupational exposure to coal dust is associated with a small mean deficit in lung function even in the absence of simple pneumoconiosis, and independently from the effects of smoking. The requirement that miners should have evidence of pneumoconiosis to qualify for compensation for impaired lung function is therefore unjustified.